Osteogenic differentiation of human umbilical cord-derived stromal cells on human amniotic membrane - Oliveira, Ana Rita Almeida, 1988- (2012)
Tese de mestrado. Biologia (Biologia Evolutiva e do Desenvolvimento). Universidade de Lisboa, Faculdade de Ciências, 2011